Principal Component Analysis and Classification of Saving Decisions for Employees in the Bank of the Lao People's Democratic Republic, Luang Prabang Province - Khruachalee, Krisada (KKBS Journal of Business Administration and Accountancy, 2020)
The development of a country through internal sources of funds resulting from savings is considered an important factor for sustainable economic driving. This research's objectives were to study the saving behavior of employees of the Bank of the Lao PDR. Moreover, we also analyze the principal components that influence employee saving behavior. Also, we construct the classification model of employee savings decisions to categorize the groups of savers according to savings scores. The population is employees of the bank of the Lao PDR in Luang Prabang province. The factor analysis will be examined by the principal component analysis method, which is orthogonally rotated by the Varimax approach. Classification modeling will be based on logistic regression analysis. The results show that most employees have savings plans because they have good fundamental knowledge in finance and investment. They have an average amount of monthly savings between 2,000,001 to 2,500,000 kip. The most popular form of savings is a saving deposit, where the main objective is to be used in an emergency. The population is interested in a saving period between 1 to 5 years. As for the principal components that influence saving behavior, we found that 52.94 percent of the total variation of the factors that influence employees' saving behavior can be explained by income, risk – tolerance, financial literature, and dependency. The overall forecasting accuracy of the model used to classify a decision of saver is 85.96 percent, which can classify the employees into 5 groups consisting of strongly interested in saving, interested in saving, rather interested in saving, rather uninterested in saving, and uninterested in saving, where their credit score is above 550, 526-550, 501-525, 475-500 and below 475 respectively.